Biological, physical and technical basics of cell engineering - Artmann, Gerhard M. (Singapore : Springer, 2018)
This book presents and discusses recent scientific progress on Cell and Stem Cell Engineering. It predominantly focuses on Biological, Physical and Technical Basics, and features new trends of research reaching far into the 21st century.
Understanding the Living State -- Self-Organizing of Molecular Machines -- The Mystery of Cellular Motors: Water and Hydrogels -- Molecular Motors in Biotechnology -- Leukocyte Guidance by Molecular Signals -- Medical Aspects of Cellular Mobility.-Structural Biology -- Computational Biophysics, Modeling -- Cell survival in hostile environments -- 3D Cell Culture and Bioreactors -- Cell-Based Hybrid Organs, Sensors, Interfaces, and Surface Interactions -- Cell-Cell Interactions -- Blood, Stem Cell, and Tissue Engineering -- Cell Mechanics and Mechanical Stress Response -- Cell Manipulation, Gene and Drug Delivery, Pharmacology -- hIPS Cell Applications in Toxicology and Pharmacology -- Neutrons at Work -- Ontogenesis Engineering.
Includes bibliographical references.
Description based on publisher-supplied MARC data.
Keywords: Biological physics; Biomaterials